Dampak Kondisi Industri dan Pergantian Auditor terhadap Kecurangan Laporan Keuangan - Sunita Dasman; Nafisah Afkar Nida (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The mining sector is one of the pillars of a country’s national economic development. In recent years the financial performance of the mining sector in Indonesia has decreased, therefore many companies are required to immediately improve their performance in order to survive by committing fraudulent financial reporting. This study aims to examine the effect of financial stability, financial target, nature of industry, and change in auditor toward fraudulent financial reporting. The sampling technique used purposive sampling method which resulted in 37 mining companies listed on the Indonesian Stock Exchange for the 2017-2020 period. The analytical method uses descriptive statistical test and logistic regression test with SPSS 25. The result of the analysis show that only financial target and nature of industry affect fraudulent financial reporting. While financial stability and change in auditor have no effect on fraudulent financial reporting. However, financial stability when interacted with financial target has an effect on fraudulent financial reporting. While nature of industry when interacted with change in auditor have no effect on fraudulent financial reporting.